Temporal variations, distribution, ecological risks, and sources of antibiotics in the marine ecosystem of Dapeng Cove, Shenzhen, South China - Su, Haochang; Li, Wenjun; Hu, Xiaojuan; Xu, Wujie; Xu, Yu; Wen, Guoliang; Cao, Yucheng (Frontiers in Marine Science, 2022)
Introduction Antibiotics are widely used in medical and health services, as well as livestock farming. High concentrations of antibiotics are eventually discarded into rivers due to incomplete metabolism and removal. Bays connect rivers to the sea, and have important ecological functions. Although the occurrence, concentrations, and distribution of antibiotics in bays have been widely studied, the temporal variations in the concentration, contamination indicators and sources of antibiotics, as well as related ecological risk factors, remain unclear. Methods Within this context, we investigate the sources, concentrations, temporal variations, and ecological risks associated with antibiotics in water and sediment samples from Dapeng Cove, Shenzhen, South China, in three rainy seasons. Results Eight and ten different antibiotics were detected in the water and sediment samples, respectively. Of these, the detection rates of erythromycin-H2O (ETM) and clarithromycin were highest in both sample types (100%), while trimethoprim (TMP) and ETM were the most abundant antibiotics in the water and sediment samples, respectively. The total concentration (TC) of antibiotics was highest in water and sediment samples from a local domestic sewage site, at 301.96 ng/L and 18.67 ng/g, respectively. Several environmental factors and the concentrations of the predominant antibiotics TMP and ETM were positively correlated. Multiple linear regression analysis revealed TMP and ETM to be the predominant antibiotics influencing the TC of the target antibiotics, with partial regression coefficients of 1.28 and 1.136, respectively (p < 0.01). Notably, ETM had risk quotients of 0.43–7.91, indicating medium to high risk, while samples from the inner bay and domestic sewage outlet had high ecological risk levels. Redundancy analysis showed that the domestic sewage and inner bay samples were clustered closely but separately from the other samples. Discussion The results of our study indicate that domestic sewage is the dominant source of antibiotics in the bay.